Inhibition of Cronobacter sakazakii in an infant simulator of the human intestinal microbial ecosystem using a potential synbiotic - Ke, Alfred; Parreira, Valeria R.; Farber, Jeffrey M.; Goodridge, Lawrence (Frontiers in Microbiology, 2022)
Powdered infant formula (PIF) can be contaminated with Cronobacter sakazakii, which can cause severe illnesses in infants. Synbiotics, a combination of probiotics and prebiotics, could act as an alternative control measure for C. sakazakii contamination in PIF and within the infant gut, but synbiotics have not been well studied for their ability to inhibit C. sakazakii. Using a Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) inoculated with infant fecal matter, we demonstrated that a potential synbiotic, consisting of 6 LAB strains and Vivinal GOS, can inhibit the growth of C. sakazakii in an infant possibly through either the production of antimicrobial metabolites like acetate, increasing species diversity within the SHIME compartments to compete for nutrients or a combination of mechanisms. The first addition of the potential synbiotic slightly increased species diversity in SHIME 3 (p ≥ 0.05) compared to the control and LAB, which may affect the survival of C. sakazakii throughout the treatment period. Our results also revealed that the relative abundance of Bifidobacterium was negatively correlated with Cronobacter in the SHIME compartment without any treatments (ρ = -0.96; p < 0.05). These findings suggest that C. sakazakii could be inhibited by the native gut microbiota, but inhibition can be accelerated by the potential synbiotic treatment.